HTA Training for Healthcare Professionals: International Overview of Initiatives Provided by HTA Agencies and Organizations - Hoxhaj, Ilda; Castagna, Carolina; Calabrò, Giovanna Elisa; Boccia, Stefania (Frontiers in Public Health, 2022)
Background Health Technology Assessment (HTA) is a multidisciplinary process that synthesizes, with a systematic, transparent, impartial and robust methodological approach, the main information on the medical, economic, ethical and social implications of the use and dissemination of a health technology. Its aim is to support decision-makers in identifying safe, effective, patient-centered and best-value health policies, in order to promote an equitable, efficient, and high-quality health system. Given the continued application of innovative technologies into clinical practice, healthcare professionals need to be able to adequately evaluate these technologies using evidence-based approaches such as HTA. Therefore, the implementation of training in HTA is crucial. The aim of this study was to investigate existing HTA training initiatives for healthcare professionals provided by international HTA agencies and organizations around the world. Methods From March to November 2020, the websites of HTA agencies and organizations belonging to the European network for HTA (EUnetHTA) and to the International Network of Agencies for HTA (INAHTA), and the website of the HTA International (HTAi), were explored for identifying the HTA training initiatives directed to healthcare professionals. In addition, we screened the training initiatives proposed at European level by EUnetHTA as part of its Joint Actions and conducted in collaboration with its public-private partners. Specific keywords were searched in English and adapted to French, Portuguese, Spanish, Italian and German. Data extraction of the retrieved training initiatives was conducted from November 2020 to February 2021 and considered the following information: agency, country, website, coordinator, type of initiative, target, topic, main contents, and language. Results Out of 124 agencies/organizations/EUnetHTA public-private partners screened, only 21 provided training initiatives for healthcare professionals. A total of 55 training initiatives were analyzed, 85.5% of which were delivered at the European level and 14.5% at the international level. The countries with a greater number of courses were: Austria, Argentina, Spain, Portugal, and the United Kingdom. Twenty-one training initiatives focused on HTA application and methodology while 34 on specific HTA domains, particularly on the economic one. The technologies covered were mainly drugs. Conclusions Our study revealed a limited number of HTA training programs targeting healthcare professionals. HTA supports the decision-making processes concerning the use and application of health technologies with scientific evidence. Indeed, training of healthcare professionals in this field should be a key driver in implementing evidence-based healthcare choices and through rigorous methodological approaches such as HTA, in order to ensure proper health governance and value-based application of technological innovations in clinical practice. Therefore, capacity building of healthcare professionals in this area should be enhanced by using appropriate and effective training initiatives and educational strategies.